Предмет: Математика,
автор: nokia6
упростить выражения 4*(7+a)+5*(a+6)= (5+y)*7+(6-y)*4= 4*(2с+d)+8*(c+d)= (m+5)*3+8*(3m+2)+5*(2m-5)= плиз решите!
Ответы
Автор ответа:
0
4*(7+a)+5*(a+6)=28+4a+5a+30=58+9a
(5+y)*7+(6-y)*4=35+7y+24-4y=59+3y
4*(2с+d)+8*(c+d)=8c+4d+8c+8d=16c+12d
(m+5)*3+8*(3m+2)+5*(2m-5)=3m+15+24m+16+10m-25=37m+6
(5+y)*7+(6-y)*4=35+7y+24-4y=59+3y
4*(2с+d)+8*(c+d)=8c+4d+8c+8d=16c+12d
(m+5)*3+8*(3m+2)+5*(2m-5)=3m+15+24m+16+10m-25=37m+6
Автор ответа:
0
спс
Автор ответа:
0
z yt vfue yfqnb
Автор ответа:
0
я не могу найти
Автор ответа:
0
а ладн пока
Автор ответа:
0
вечерком встретимся
Похожие вопросы
Предмет: Английский язык,
автор: kandakova0400
Предмет: Математика,
автор: hakovartem
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: Vikulekpytkova
Предмет: Алгебра,
автор: loloTRY